Key Performance Indicator: Concept, Implementation to Performance Management - Harry Purwoko; Kamsariaty; Rubadi; Joned Ceilendra Saksana; Josua Panatap Soehaditama (East Asian Journal of Multidisciplinary Research, 2023)
This article contributes to Key Performance Indicator (KPI) is an existing application of various studies derived from existing literature. This scientific article uses qualitative as a method, which is illustrated from scientific articles from journals, books, and other sources that make literature sources in supporting this article so as to provide a result. This scientific article provides a result and recommendation, namely providing application or implementation, especially the field of human resource science involved from various industries in scientific articles as the literature used. It is very necessary that with the gap in performance management that has not been thoroughly discussed related to the existing Key Performance Indicators, other researchers in the future can continue the results of this scientific article.